Original paperNutritive value of daily food rations of patients with psoriasis vulgaris: a preliminary report - Wasiluk, Diana; Stefanska, Ewa; Ostrowska, Lucyna; Serwin, Agnieszka Beata; Klepacki, Andrzej; Chodynicka, Bozena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Psoriasis is a chronic inflammatory systemic disorder. It has been suggested that dietary factors may influence the course and severity of the disease. Aim : To assess nutritive values of daily food rations (DFRs) of patients with psoriasis vulgaris and to correlate them with the severity of the disease, as well as to compare them with DFRs of patients with other chronic inflammatory skin disorders. Material and methods : The study was conducted among 39 out-patients with psoriasis vulgaris and 18 patients with other chronic inflammatory skin disorders. The severity of psoriasis was assessed using the Psoriasis Area and Severity Index (PASI). The dietary habits were evaluated using a 24-hour interview. The energetic and nutritive value of DFRs were calculated using Dieta 2 software and the statistical analysis was performed using Statistica 9.0 software. Results : Daily food rations in psoriasis patients were characterized by an excessive intake of fats and energy derived from fats in both groups. Males and females with psoriasis consumed more monounsaturated fatty acids than controls. The PASI value in females correlated with the total intake of fatty acids and that of monounsaturated fatty acids. The intake of vitamin D3 in females of both groups was very low. Conclusions : The nutritive value of DFRs both in psoriasis patients and in controls was imbalanced taking into consideration various nutrients.